Network pharmacology reveals that Berberine may function against Alzheimer’s disease via the AKT signaling pathway - Wei, Wei; Yao, Jiu-xiu; Zhang, Ting-ting; Wen, Jia-yu; Zhang, Zhen; Luo, Yi-miao; Cao, Yu; Li, Hao (Frontiers in Neuroscience, 2023)
Objective To investigate the mechanism underlying the effects of berberine (BBR) in the treatment of Alzheimer’s disease (AD). Methods 3 × Tg AD mice were treated with BBR for 3 months, then the open field test (OFT), the novel object recognition test (NOR) and the Morris water maze (MWM) test were performed to assess behavioral performance. Hematoxylin–eosin (HE) staining, Nissl staining were used to examine histopathological changes. The pharmacological and molecular properties of BBR were obtained from the TCMSP database. BBR-associated AD targets were identified using the PharmMapper (PM), the comparative toxicogenomics database (CTD), DisGeNet and the human gene database (GeneCards). Core networks and BBR targets for the treatment of AD were identified using PPI network and functional enrichment analyses. AutoDock software was used to model the interaction between BBR and potential targets. Finally, RT-qPCR, western blotting were used to validate the expression of core targets. Results Behavioral experiments, HE staining and Nissl staining have shown that BBR can improve memory task performance and neuronal damage in the hippocampus of AD mice. 117 BBR-associated targets for the treatment of AD were identified, and 43 genes were used for downstream functional enrichment analysis in combination with the results of protein–protein interaction (PPI) network analysis. 2,230 biological processes (BP) terms, 67 cell components (CC) terms, 243 molecular function (MF) terms and 118 KEGG terms were identified. ALB, EGFR, CASP3 and five targets in the PI3K-AKT signaling pathway including AKT1, HSP90AA1, SRC, HRAS, IGF1 were selected by PPI network analysis, validated by molecular docking analysis and RT-q PCR as core targets for further analysis. Akt1 mRNA expression levels were significantly decreased in AD mice and significantly increased after BBR treatment (p < 0.05). Besides, AKT and ERK phosphorylation decreased in the model group, and BBR significantly increased their phosphorylation levels. Conclusion AKT1, HSP90AA1, SRC, HRAS, IGF1 and ALB, EGFR, CASP3 were core targets of BBR in the treatment of AD. BBR may exert a neuroprotective effect by modulating the ERK and AKT signaling pathways.